Genetic diversity of Hapalogenys analis in the northwest Pacific assessed using dd-RAD sequencing - Zhang, Qun; Sun, Cheng-He; Huang, Jin-Long; Lao, Ye-Ling; Chang, Xi-Yue; Cao, Jia-Ning (Frontiers in Ecology and Evolution, 2024)
The broad-banded velvetchin Hapalogenys analis is an economically and scientifically important global temperate and tropical nearshore marine fish. To understand the genetic evolution mechanism of H. analis, simplified genome sequencing analysis was conducted on 82 samples of H. analis from three populations (Akashi, Zhoushan, and Shantou) in the northwestern Pacific Ocean using double-digest restriction site-associated DNA sequencing. Genetic characteristics were identified using single-nucleotide polymorphism loci, and a small fragment library (250–450 bp long) was constructed for double-end sequencing. Single-nucleotide polymorphisms (SNPs) were detected using Stacks software and analyzed. The phylogenetic tree was constructed to analyze the population structure characteristics and the genetic evolutionary relationships between individuals in different regions at the genetic level. The sequencing library constructed for 82 samples of H. analis using double-digest restriction site-associated DNA sequencing possessed an average of 7,931,195 sequencing sequences and an average of 1,141,560,806 bases in the 82 samples. A total of 3,204,106 SNP loci were obtained from the three populations of H. analis, indicating rich genetic diversity. The transition to transversion ratio of SNPs was >1.5, indicating transformational reversal bias in H. analis. The observed heterozygosity of the various populations was 0.186–0.199, with an expected heterozygosity of 0.253–0.268. High diversity in all three populations was detected using nucleotide diversity analysis. AS and ZS had the highest degree of differentiation. The H. analis samples shared two gene libraries; some populations were closely related, whereas others had a distant genetic relationship. The results of genetic statistics, genetic differentiation, population structure, principal component, phylogenetic, and genetic relationship analyses supported independent clustering of the AS population, which can be used as a new genetic resource for conserving H. analis. These results provide a reference basis for comparative genomics studies of H. analis and rational utilization of Hapalogenys resources.